A “Ópera do Malandro” de Chico Buarque de Hollanda: uma metáfora do cenário brasileiro na década de 1970 - Moscardo , Gleiciele Mendes Viana (2012)
This research addresses the musical comedy "Opera do Malandro" composed by Chico Buarque in 1978 and set during 40´s , at Rio de Janeiro, the final phase of the Estado Novo (1937-45). This investigation considers how Chico Buarque, using poetry and music, handled the censorship during the military dictatorship of the 70´s. It inserts "Opera do Malandro" in the context of the military dictatorship of the 70´s, considering the inclusion of multiple times in the preparation of the piece; the processes of hybridization that resulted in the "Opera do Malandro" and yet, the processes of identity representations, in particular those embodied in the figure of the rascal. Meaning to elucidate these questions, based on the concepts of phenomenological analysis and seeking support for the relationship between lyrics and music in musical rhetoric and Luiz Tatit´s studies, an analysis was made of the following poetic-musical songs that composes the piece: “O Malandro”, “Homenagem ao Malandro”, “Ópera” e “O Malandro nº2”. The analysis and interpretation of the query have confirmed the hypothesis presented that, from a language of "cracks" centered on the image of the rascal and the game of temporalities and hybridizations, Chico Buarque, using metaphores, presented the political, social and economic conditions of the country at those years, the 70´s.